2013
DOI: 10.1371/journal.pone.0059991
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Blood Testosterone and Childhood Internalizing and Externalizing Behavior: A Prospective Study

Abstract: Antenatal testosterone exposure influences fetal neurodevelopment and gender-role behavior in postnatal life and may contribute to differences in developmental psychopathology during childhood. We prospectively measured the associations between umbilical cord blood testosterone levels at birth and childhood behavioral development in both males and females from a large population based sample. The study comprised 430 females and 429 males from the Western Australian Pregnancy Cohort (Raine) Study where umbilica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…as assessed with the SDQ. This implication of the present study concurs with a prior study showing no strong or consistent relationships between umbilical cord blood testosterone and emotional or behavioral problems in typically-developing young children (Robinson et al, 2013) and also concurs with prior research showing no differences in emotional or behavioral problems between children and adolescents with CAH and their unaffected relatives (Berenbaum et al, 2004). Moreover, on average, both girls with CAH and unaffected sisters in the current study showed increased externalizing and psychosocial problems in comparison with girls in the general population, suggesting that social influences, such as familial processes or social stigma, play a stronger role than endocrine influences in the development of psychological difficulties in these children.…”
Section: Endocrine Influencessupporting
confidence: 92%
“…as assessed with the SDQ. This implication of the present study concurs with a prior study showing no strong or consistent relationships between umbilical cord blood testosterone and emotional or behavioral problems in typically-developing young children (Robinson et al, 2013) and also concurs with prior research showing no differences in emotional or behavioral problems between children and adolescents with CAH and their unaffected relatives (Berenbaum et al, 2004). Moreover, on average, both girls with CAH and unaffected sisters in the current study showed increased externalizing and psychosocial problems in comparison with girls in the general population, suggesting that social influences, such as familial processes or social stigma, play a stronger role than endocrine influences in the development of psychological difficulties in these children.…”
Section: Endocrine Influencessupporting
confidence: 92%
“…We have recently reported that higher cord testosterone concentrations are associated with behavioural problems in early childhood. Attention difficulties in males and withdrawal symptoms in females were both negatively related to cord blood testosterone levels [39]. Together, these data suggest that umbilical cord blood is a valid method for examining early-life sex steroid exposure.…”
Section: Introductionmentioning
confidence: 73%
“…First, Lutchmaya and colleagues analysed males and females together, and although sex was controlled in the analyses, there is emerging evidence that males and females respond differently to circulating sex steroid concentrations [53], as evidenced by different associations identified for males and females [19,25,27,39,55]. Therefore, males and females should be separated in association analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, umbilical cord blood is obtained immediately after delivery, and its hormone levels are broadly considered to reflect the hormonal environment of the fetus at late gestation [ 9 , 10 ]. Previous studies have been performed using cord blood to investigate the relationship between fetal hormonal exposure and human development [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%